HeLLePhant: A phantom mimicking non-small cell lung cancer for texture analysis in CT images. (May 2022) - Rinaldi, Lisa; Pezzotta, Federico; Santaniello, Tommaso; De Marco, Paolo; Bianchini, Linda; Origgi, Daniela; Cremonesi, Marta; Milani, Paolo; Mariani, Manuel; Botta, Francesca
Highlights: Phantoms are a useful tool to study feature repeatability and reproducibility. The proposed phantom contains heterogeneous inserts to mimic lung tumour texture. A commercial phantom with homogeneous inserts is not suitable to mimic tumours. Feature repeatability is texture dependent. Most features are repeatable, especially from firstorder and glcm categories. Abstract: Purpose: Phantoms mimicking human tissue heterogeneity and intensity are required to establish radiomic features robustness in Computed Tomography (CT) images. We developed inserts with two different techniques for the radiomic study of Non-Small Cell Lung Cancer (NSCLC) lesions. Methods: We developed two insert prototypes: two 3D-printed made of glycol-modified polyethylene terephthalate (PET-G), and nine with sodium polyacrylate plus iodinated contrast medium. The inserts were put in a handcraft phantom (HeLLePhant). We also analysed four materials of a commercial homogeneous phantom (Catphan® 424) and collected 29 NSCLC patients for comparison. All the CT acquisitions were performed with the same clinical protocol and scanner at 120kVp. The HeLLePhant phantom was scanned ten times in fixed condition at 120kVp and 100kVp for repeatability investigation. We extracted 153 radiomic features using Pyradiomics. To compare the features between phantoms and patients, we computed how many phantom features fell in the range between 10th and 90th percentile of the corresponding patient values. We deemed repeatable the features with a coefficient of variation (CV) less than or equal to 0.10. Results: The best similarity with the patients was obtained with the polyacrylate inserts (55.6–90.2%), the worst with Catphan (15.7–19.0%). For the PET-G inserts 35.3% and 36.6% of the features match the patient range. We found high repeatability for all the inserts of the HeLLePhant phantom (74.3–100% at 120kVp, 75.7–97.9% at 100kVp), and observed a texture dependency in repeatability. Conclusions: Our study shows a promising way to construct heterogeneous inserts mimicking a target tissue for radiomic studies.